Enhancement of Indonesian High School Student Conceptual Mastery on VSEPR Topic Using Virtual Simulation of Molecule Shapes: A Case Study of Quasi-Experimental Evidence - Stiawan, E.; Basuki, R.; Liliasari, L.; Rohman, I. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
The Valence Shell Electron Pair Repulsion (VSEPR) is an essential topic for high school student’s fundamental understanding of 3D shapes of chemical compounds. Due to the spatial aspect of the topic, the students were forced to imagine the geometry of the molecule by predicting the free or bonded electron pair repulsion. Suitable learning media to accommodate those features should be precisely selected to help students properly understand the geometry of the molecule based on the VSEPR topic. This study compared the significant difference in the application of two media of animation video and interactive simulation toward the control and experimental groups, respectively, to enhance conceptual mastery of the VSEPR topic. This study was a statistical quasi-experiment study with two classes of control (animation video) and experimental (interactive simulation) groups. The results of the significant difference test of the groups showed that the distribution of the experimental and control groups was not normal (significantly different) and normal (not significantly different), respectively. Analysis results using Mann-Whitney for the non-parametric free two samples comparative test with a 95% confidence level showed that the application of virtual simulation on the experimental group impacted more in improving the conceptual mastery of the VSEPR topic. Furthermore, there was an identified significant improvement in sub-concepts of the VSEPR topic in binding pair, molecular shape, and electron repulsion. These findings could support the teachers in designing lesson plans for students to master the VSEPR topic.